Pengaruh Kegiatan Seni Tari Kreasi terhadap Kepercayaan Diri Anak Usia 4-5 Tahun di TK Pertiwi Desa Buluh Kasab - Riska Fitriyanti; Asih Nur Ismiatun; Indra Gunawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effect of creative dance activities on the self-confidence of children aged 4–5 years at TK Pertiwi, Buluh Kasab Village. The background of this study is the low level of children’s self-confidence, which is reflected in passive behavior, reluctance to perform in front of the class, and a lack of courage to express themselves in front of others. This research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. Data were collected through structured observation, while data analysis was conducted by calculating pretest and posttest scores, which were then analyzed using a paired sample t-test and effect size calculation to determine the strength of the treatment effect. The creative dance activities were implemented over six sessions by integrating elements of music, movement, and expression using two children’s songs, namely “Percaya Diri” by Abita and “Aku Bisa” by AFI Junior. The results indicated a significant improvement in children’s self-confidence, as shown by an increase in the mean score from 15.08 in the pretest to 32.75 in the posttest. The t-test results revealed a t-value of −31.006 with a significance level of 0.000 (p < 0.05). An effect size value of 6.43 indicated a very strong effect. Therefore, creative dance activities have a significant impact on enhancing early childhood self-confidence and are recommended as an effective learning strategy.